2006
DOI: 10.1016/j.tsf.2005.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Large-grained polycrystalline silicon on glass for thin-film solar cells

Abstract: We have investigated the formation of large-grained polycrystalline silicon (poly-Si) films on glass for thin-film solar cells using the 'seed layer concept' which is based on the epitaxial thickening of a thin large-grained poly-Si template (seed layer). Due to the glass substrate all

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…Details of this process have been presented elsewhere [1]. Briefly, a 300 nm thick Al film was deposited by DC magnetron sputtering onto Schott Borofloat33 glass.…”
Section: Seed Layer Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of this process have been presented elsewhere [1]. Briefly, a 300 nm thick Al film was deposited by DC magnetron sputtering onto Schott Borofloat33 glass.…”
Section: Seed Layer Preparationmentioning
confidence: 99%
“…This layer was removed by chemical-mechanical polishing (CMP) to form a smooth, poly-Si film on the glass substrate with an average surface roughness ðR a Þ of o0:5 nm and a thickness of about $100 nm. The film is characterised by large grains (up to $10 mm) and a preferred (1 0 0) orientation [1,2].…”
Section: Seed Layer Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pc-Si thin film can be applied in many areas such as solar cells [1][2][3], thin film transistors (TFTs) [4] and flat panel displays. The general strategy of fabricating the pc-Si thin film is to recrystallize the amorphous silicon (α-Si) previously deposited on a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, strongly (001) preferred orientation can be achieved at a low annealing temperature (below 400°C) and this orientation will recede when temperature rises [15]. Gall et al [3] reported that (001) orientation was obviously weakened (dropped to 60% of total grains) as annealing temperature went to 450°C. By contrast, (111) preferred orientation is supposed to be achieved at a higher annealing temperature.…”
Section: Introductionmentioning
confidence: 99%